(untitled) (Jurnal Agregasi : Aksi Reformasi Government dalam Demokrasi, 2020)
Abstract This study aims to identify and analyze the trade business license services small classification and to analyze factors that affect the application of principle of trade business license services small classification in Singingi Hilir office, Kuantan Singingi District. This study used a qualitative research method with a literature review or previous research process. The data used were selected from the last 9 years journal issues from 2010 to 2018. The journals used were the journal scopus with the highest citation, the journals used were journals relevant to government activities. Research and analysis results from 30 journals from 2010 to 2018 and the results of interviews with research informants produced mixed and varied data. It would be elaborated in parts so it did not lead to inequality results. Based on the search results with Word Frequency Query feature of the NVivo 12 QSR software from various data sources that have been imported from 30 sources of research journals, the word ’Government’ is the word with the most frequency appearing, 2,848 words from all research data source journals. The interview showed that the information of trade business license services transparency in Singingi Hilir District had been given clearly to the community and according to established procedures.